Protein corona formation in bronchoalveolar fluid enhances diesel exhaust nanoparticle uptake and pro-inflammatory responses in macrophages. Issue 7 (8th August 2016) - Shaw, Catherine A.; Mortimer, Gysell M.; Deng, Zhou J.; Carter, Edwin S.; Connell, Shea P.; Miller, Mark R.; Duffin, Rodger; Newby, David E.; Hadoke, Patrick W.F.; Minchin, Rodney F.
Abstract: In biological fluids nanoparticles bind a range of molecules, particularly proteins, on their surface. The resulting protein corona influences biological activity and fate of nanoparticle in vivo . Corona composition is often determined by the biological milieu encountered at the entry portal into the body, and, can therefore, depend on the route of exposure to the nanoparticle. For environmental nanoparticles where exposure is by inhalation, this will be lung lining fluid. This study examined plasma and bronchoalveolar fluid (BALF) protein binding to engineered and environmental nanoparticles. We hypothesized that protein corona on nanoparticles would influence nanoparticle uptake and subsequent pro-inflammatory biological response in macrophages. All nanoparticles bound plasma and BALF proteins, but the profile of bound proteins varied between nanoparticles. Focusing on diesel exhaust nanoparticles (DENP), we identified proteins bound from plasma to include fibrinogen, and those bound from BALF to include albumin and surfactant proteins A and D. The presence on DENP of a plasma-derived corona or one of purified fibrinogen failed to evoke an inflammatory response in macrophages. However, coronae formed in BALF increased DENP uptake into macrophages two fold, and increased nanoparticulate carbon black (NanoCB) uptake fivefold. Furthermore, a BALF-derived corona increased IL-8 release from macrophages in response to DENP from 1720 ± 850 pg/mL to 5560 ± 1380 pg/mL ( p = 0.014). These results demonstrate that the unique protein corona formed on nanoparticles plays an important role in determining biological reactivity and fate of nanoparticle in vivo . Importantly, these findings have implications for the mechanism of detrimental properties of environmental nanoparticles since the principle route of exposure to such particles is via the lung.